Sounds in translation Intersections of music, technology and society - Chan, Amy (ANU Press, 2009)
Sounds in Translation: Intersections of music, technology and society joins a growing number of publications taking up R. Murray Schafer's challenge to examine and to re-focus attention on the sound dimensions of our human environment. This book takes up his challenge to contemporary audiologists, musicologists and sound artists working within areas of music, cultural studies, media studies and social science to explore the idea of the 'soundscape' and to investigate the acoustic environment that we inhabit. It seeks to raise questions regarding the translative process of sound: 1) what happens to sound during the process of transfer and transformation; and 2) what transpires in the process of sound production/expression/performance. Sounds in Translation was conceived to take advantage of new technology and a development in book publishing, the electronic book. Much of what is written in the book is best illustrated by the sound itself, and in that sense, permits sound to 'speak for itself'.